Biochemical study of venom sea anemone Phymactis papillosa (Actiniidae) - Cuya, Antony (2017)
In this work, the poison of Phymactis papillosa collected in Ancón bay has been studied biochemically. The venom was obtained by hypotonic shock and then lyophilized. Electrophoretic analysis of the soluble poison showed the presence of 5 protein bands with molecular weights between 5 and 25.1 kDa.The soluble venom was fractionated by filtration chromatography on a Sephadex G-50 column, yielding four protein peaks (I, II, III and IV). In the soluble venom and collected fractions was measured protease activity, phospholipase, hyaluronidase, acid phosphatase and alkaline phosphatase; as well as hemolytic and neurotoxic activity. Proteolytic activity on casein was found in the soluble venom and peaks I and III. Was not detected phospholipase activity, hyaluronidase, acid phosphatase and alkaline phosphatase. Hemolytic activity on human red cells tested, was found in the soluble venom and peak II. Finally, the soluble venom as the peak III showed be neurotoxic when injected into white mice intraperitoneally. It is concluded that the soluble venom of P. papillosa has proteolytic, hemolytic and neurotoxic activity.